Bimbingan Teknis Penulisan Buku dan Sosialisasi Hak Kekayaan Intelektual di Institut Agama Islam Hidayatullah Batam - Syamsidah Lubis; Muthma'innah Muthma'innah; Sari Mahwati Hasibuan; M. Sidik; Mohammad Ramli (LPPM-IAI Hidayatullah Batam, 2026)
Book Writing and HKI (Intellectual Property Rights) show a close relationship between the two, Books are intellectual works protected by law. Books that have been written and realized in tangible form, in the form of digital or printed manuscripts, and will obtain copyright protection according to applicable regulations. Copyright is the exclusive right of the author to publish and distribute books, and grant permission to use them to other parties. The community service carried out was in the form of Technical Guidance (Bimtek) to lecturers and the campus community of the Hidayatullah Islamic Institute of Batam. This Bimtek aims to increase knowledge and help lecturers to be productive in writing books, both textbooks and reference books. The output of the community service in the form of Bimtek is that lecturers produce works in the form of books every semester and these books will be used as lecture materials and references for students in lectures. The method used is the Participation Action Research (PAR) method. The results of the Technical Guidance show that assistance from the beginning of the book in the form of a cover, book framework in the form of a table of contents and others, book preparation and Copyright is carried out with Focus Group Discussions (FGD) or group discussions and focuses on the field of science or scientific group of lecturers and selecting topics developed from the RPS in the courses taught by lecturers and resource persons guide lecturers in writing books and socializing HKI.